Pilot investigation of a novel white matter imaging technique in Veterans with and without history of mild traumatic brain injury. (24th August 2018) - Jurick, Sarah M.; Hoffman, Samantha N.; Sorg, Scott; Keller, Amber V.; Evangelista, Nicole D.; DeFord, Nicole E.; Sanderson-Cimino, Mark; Bangen, Katherine J.; Delano-Wood, Lisa; Deoni, Sean; Jak, Amy J.
ABSTRACT: Objective: The objective of this study is to assess utility of in vivo myelin imaging in combat Veterans with and without history of mild traumatic brain injury (mTBI). We hypothesized that those with history of mTBI would have lower myelin water fraction (MWF), a marker of myelin integrity and content, than those without, and lower MWF would be associated with worse speeded attention/processing speed. Research design: Combat Veterans ( N = 70) with ( n = 42) and without history of mTBI ( n = 28) underwent neuroimaging including a novel myelin-sensitive magnetic resonance imaging technique (multicomponent-driven equilibrium single-pulse observation of T1/T2; mcDESPOT) and comprehensive neuropsychological assessment. Results: There were no group differences in MWF using a region-of-interest approach. An exploratory analysis applying limited spatial constraints, however, revealed significantly more 'potholes' (clusters of low MWF) in Veterans with history of mTBI compared to those without. Lower MWF across several ROIs was associated with worse performance on a speeded attention task across groups. Conclusion: Veterans in the post-acute period following mTBI showed limited and spatially heterogeneous MWF changes and myelin integrity was significantly related to processing speed. This preliminary evidence for usefulness of mcDESPOT in combat Veterans with history of mTBI warrants future research to determine mcDESPOT's relative utility compared to techniques such as diffusion tensor imaging.